Literacy scholars coming to know the people in the parks, their literacy practices and support systems. Issue 2 (3rd April 2019) - Tinker Sachs, Gertrude; McGrail, Ewa; Lewis Ellison, Tisha; Dukes, Nicole Denise; Walsh Zackery, Kathleen
ABSTRACT: In this research, literacy scholars present the voices of the people who live in the parks near their state capital and university in a south-eastern city in the United States. Through the recorded, transcribed and analyzed conversations, we report the literacy practices of the people in the parks and their insights into the nested state and university structures that restrict and empower their quality of life opportunities. The general findings show our participants to be avid readers of a variety of genres and users of technology but with limited access to state and university resources and infrastructures due to laws and regulations and community members' negative perceptions that restrict their use. Recommendations are made for more urban community state and university collaborative initiatives to increase understandings and respect for people who live in the parks to honor their motivations for greater social capital and attainment of their life goals.